The Impact of Types of Issues, Sectors, Lifespan and Different Economic Periods on the Short-Run and Long-run Performance of IPOs - Tapa, Afiruddin (2003)
This study examines the performance of initial public offerings (IPOs) of 157 KLSE Main Board Companies for the period 1990 to 1999. The performance of the IPOs is analysed based on sample classification of types of issues, sectors in the Kuala Lumpur Stock Exchange (KLSE), the lifespan of a company and different economic conditions. Both the short-run and long-run performances were analysed. This study documents an average first day initial return of 88.11%. This is consistent with previous studies which reported that most IPOs are generally underpriced on their first day of trading. Furthermore, the evidence shows that the average abnormal returns in the long-run are smaller than those in the short-run. There is substantial variation in the performance of IPOs across sectors in the Main Board of the KLSE. The Property, Industrial Product and Construction sectors reported the highest initial returns (above 100%).The fmding shows a significant difference in the mean initial returns under different economic conditions. In the hot market, Malaysian IPOs recorded a higher return (127.96%) than in the cold market (27.04%). With respect to lifespan, the number of years existing does not affect the level of initial return of the IPOs. There is no significant difference in initial returns among three types of issues namely public issues, offer for sale and hybrid of public issues and offer for sale. This finding is inconsistent with the documented evidence in the developed markets.